Gender-based stigma and the prevention and treatment of HIV/AIDS among older women: A scoping review protocol. - Thi Vu; Jasmine Manalel; Kate Nyhan; Katie Wang; Joan Monin (PLoS ONE)
Introduction The population of women aged 50 years and older living with HIV is increasing. Older women face unique challenges in the prevention and management of HIV; however, they are often under engaged in HIV/AIDS research. One such challenge is gender-based stigma, which can be manifested through harmful gendered stereotypes, discrimination, prejudice, and sexism that could potentially hinder HIV care engagement among this population. We propose a scoping review to identify and synthesize evidence pertaining to how experiences of gender-based stigma impacts HIV prevention and care among older women. Materials and methods We will use the framework by Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) to conduct this scoping review. We will search MEDLINE/PubMed, Web of Science, PsycINFO, CINAHL and Scopus for empirical literature published between January 1981 and the date of search commencement. Supplementary screening will be conducted using backwards citation chaining of the final list of included full-text articles. Two reviewers will independently screen all titles and abstracts for articles that meet the predetermined inclusion criteria. Two reviewers will also screen full-text articles and chart data using a standardized data collection form. Results We will synthesize the findings through tables, charts, and narrative summaries. We will also identify gaps in the current literature and provide recommendations for future research. Findings will be shared at conferences and submitted to a peer-reviewed publication. Discussion To our knowledge, this will be the first scoping review to examine gender-based stigma in relation to HIV prevention and care among older women. We anticipate that our results will be of interest to older women living with HIV, healthcare providers, policy makers, and community activists working to improve quality of life and care experiences for older women living with HIV.